Abstracts from the 7th IFPA Conference World Psoriasis & Psoriatic Arthritis Conference - No authors listed (Medical Journals Sweden, 2024)
Abstracts from the 7th IFPA Conference World Psoriasis & Psoriatic Arthritis Conference